AI-Driven Enterprise Transformation through Cloud-Native Architecture, Intelligent Automation, Cybersecurity Governance, and Predictive Analytics (International Journal of Engineering & Extended Technologies Research (IJEETR), 2024)
Artificial Intelligence (AI) is transforming modern enterprises by enabling organizations to improve operational efficiency, strengthen decision-making, enhance customer experiences, and achieve sustainable competitive advantages. The integration of cloud-native architecture, intelligent automation, cybersecurity governance, and predictive analytics has emerged as a foundational framework for digital transformation. Cloud-native technologies provide scalable, flexible, and resilient infrastructures that support AI-driven applications and data-intensive operations. Intelligent automation combines AI, machine learning, robotic process automation, and cognitive computing to streamline business processes and reduce human intervention in repetitive tasks. Simultaneously, cybersecurity governance ensures the protection of critical digital assets, regulatory compliance, and organizational resilience against evolving cyber threats. Predictive analytics leverages historical and real-time data to forecast trends, optimize resource allocation, and support strategic decision-making. Together, these technological pillars create a comprehensive ecosystem that enables enterprises to innovate rapidly while maintaining security and operational stability. This essay examines the role of AI-driven enterprise transformation through the convergence of cloud-native architecture, intelligent automation, cybersecurity governance, and predictive analytics. It explores theoretical foundations, current research developments, implementation methodologies, organizational implications, and future opportunities. The analysis demonstrates how integrated digital capabilities facilitate enterprise agility, innovation, and long-term value creation in an increasingly complex and data-driven business environment
Keywords: Artificial Intelligence; Enterprise Transformation; Cloud-Native Architecture; Intelligent Automation; Cybersecurity Governance; Predictive Analytics; Digital Transformation; Machine Learning; Cloud Computing; Business Intelligence; Data Analytics; Cybersecurity; Organizational Innovation